2010
DOI: 10.1203/00006450-201011001-00463
|View full text |Cite
|
Sign up to set email alerts
|

463 Passive Distraction is the Only Determinant of Pain During Venous Blood Sampling in School Children in An Outpatient Clinic Setting

Abstract: Introduction: Effective implementation of an evidence based pain policy for children is affected by nurses' knowledge of, attitudes towards and selfefficacy. Since nurses from different departments and with different levels of education manage pain in children, we evaluated the impact of the nursing ward and educational level on the management of paediatric pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…However, in our study, MSSE isolates harbored more ACME (83.3%) than MRSE isolates (67.7%), which is in line with the study of Granslo et al [38], in which a significantly lower rate of methicillin and gentamicin resistance was observed between ACME-positive versus ACME-negative S. epidermidis isolates. No association between ACME and SCC mec type IV in S. epidermidis was found in our study, which is also similar to the results of Granslo et al [38]. It is suggested that the recombinases used to integrate ACME and SCC mec into the bacterial chromosome are able to integrate these 2 genetic elements independently, and different selection mechanisms may apply for S. aureus and S. epidermidis .…”
Section: Discussionsupporting
confidence: 93%
“…However, in our study, MSSE isolates harbored more ACME (83.3%) than MRSE isolates (67.7%), which is in line with the study of Granslo et al [38], in which a significantly lower rate of methicillin and gentamicin resistance was observed between ACME-positive versus ACME-negative S. epidermidis isolates. No association between ACME and SCC mec type IV in S. epidermidis was found in our study, which is also similar to the results of Granslo et al [38]. It is suggested that the recombinases used to integrate ACME and SCC mec into the bacterial chromosome are able to integrate these 2 genetic elements independently, and different selection mechanisms may apply for S. aureus and S. epidermidis .…”
Section: Discussionsupporting
confidence: 93%
“…epidermidis isolates in different geographical regions. In this study, there was no association between antibiotic resistance and the presence of ACME genes similar to the findings of other studies [ 45 , 46 ]. Surprisingly ACME positive isolates were more common among the non-sepsis group than the sepsis group.…”
Section: Discussionsupporting
confidence: 92%
“…epidermidis reported by Barbier et al ., [ 17 ]. In contrast, Granslo et al ., [ 45 ] detected all three ACME types in S . epidermidis isolates that they studied suggesting differences in ACME carriage in S .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of ACME have tended to focus on its potential virulence role in S. aureus , although this particular role is still unclear (Diep et al, 2008; Joshi et al, 2011; Montgomery et al, 2009). In S. epidermidis , ACME has been reported to be highly prevalent among carriage isolates (Barbier et al, 2011) and associated with low levels of antibiotic resistance and pathogenicity (Granslo et al, 2010). …”
Section: Discussionmentioning
confidence: 99%